2014
DOI: 10.1017/s0007114514003134
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cafeteria feeding during lactation in the rat on novel object discrimination in the offspring

Abstract: There is increasing evidence that hyperenergetic diets have an impact on memory in rodents. However, it is largely unknown how diets, such as a cafeteria diet (CD), that mimic a Western-type diet act on learning and memory, in particular when fed during early stages of development. Here, we fed lactating dams a CD and exposed both male and female offspring to a novel object discrimination (NOD) task, a two-trial test of recognition memory in which rats exposed to two identical objects during a training/familia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 45 publications
3
21
1
Order By: Relevance
“…Cafeteria feeding led to a significant increase of energy intake in lactating dams that was due to overconsumption of sugar and fat, whereas protein intake was reduced. These changes in energy and macronutrient intake are in line with previous data from our laboratories, indicating robustness of the feeding model (Akyol et al, 2012; Wright et al, 2014). This imbalance in lactational diet caused changes in offspring open‐field behaviour and, to a lesser extent, in the elevated plus maze.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Cafeteria feeding led to a significant increase of energy intake in lactating dams that was due to overconsumption of sugar and fat, whereas protein intake was reduced. These changes in energy and macronutrient intake are in line with previous data from our laboratories, indicating robustness of the feeding model (Akyol et al, 2012; Wright et al, 2014). This imbalance in lactational diet caused changes in offspring open‐field behaviour and, to a lesser extent, in the elevated plus maze.…”
Section: Discussionsupporting
confidence: 90%
“…In rodents, cafeteria diets have been shown to change a variety of behaviours, often in a sex‐specific manner (Murphy and Mercer, 2013; Warneke et al, 2014; Wright et al, 2011a, 2014). In a series of experiments, we previously demonstrated that feeding a cafeteria diet during lactation leads to reduced anxiety, but also to changes in satiety and, gender‐ depending, effects on memory in the offspring when tested at adult age (Wright et al, 2011a,b, 2014). Although these results suggest nutritional programming of behaviour, less is known about the more immediate behavioural consequences of early postnatal exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Feeding schedules are typically initiated before (e.g., pre-pregnancy obesity) or at the start of gestation and/or lactation to distinguish the effects of pre- and peri-natal high fat exposure on brain plasticity and development [20,21]. In most cases, offspring are maintained on a low fat control diet, although some experiments have also fed the offspring the same high fat diet as the mother to determine the effect of sustained high fat diet exposure [22,23,24,25,26].…”
Section: Cognitive Function and Mental Health In Offspring Born Tomentioning
confidence: 99%
“…This effect was also observed in offspring exposed to a high fat diet throughout both the pre- and postnatal period, who showed decreased retention times, higher escape latencies, and less time spent in the target quadrant of the water maze, suggesting impaired spatial memory performance [22,24,25,26]. Similarly contradictory findings have been described using the novel object recognition task, with one experiment reporting decreased exploration of the novel object in young adult male—but not female—offspring of obese dams [44] and another reporting higher initial novel exploration by male offspring exposed to a cafeteria diet during lactation [21]. Again, these discrepancies may relate to the timing of dietary exposure, sex, and age of offspring at testing.…”
Section: Cognitive Function and Mental Health In Offspring Born Tomentioning
confidence: 99%
“…While the effects of perinatal dietary fat on cognition have been studied extensively, data about the impact of a perinatal Western diet, which is high in both saturated fat and refined sugars, are scarce and equivocal (11, 12). Yet in our modern Western societies, excessive consumption of fat is frequently associated with the consumption of excessive amounts of sugars (13).…”
mentioning
confidence: 99%